The effectiveness of using blended learning in higher education: students’ perception - Abdurrahman G. Al-Mekhlafi; Essam Zaneldin; Waleed Ahmed; Hamda Y. Kazim; Mausmi D. Jadhav (Cogent Education)
Blended learning (BL) has gained popularity in higher education. However, issues such as readiness, technological infrastructure, and effective implementation remain underexplored. This study examines students’ perception of the effectiveness of BL to provide a comprehensive understanding of the dynamics surrounding BL implementation and management at the United Arab Emirates University (UAEU). The study focuses on addressing the issues associated with BL by investigating students’ perceptions of the readiness level for BL implementation including the effectiveness and available technologies. A quantitative and qualitative method was used to answer three research questions related to these two issues. The study sample included 136 undergraduate female students registered in BL courses. A questionnaire survey was used to collect quantitative data, supported by qualitative interviews. Descriptive statistics and thematic analysis were conducted to analyze the data. Most students showed positive impact of BL on their learning and positive overall effectiveness. This could be due to students’ technology readiness, positive perception of the utility of technology, and high engagement in classes. Instructors’ recommendations on implementing BL are discussed. The study also explored the factors influencing BL effectiveness, highlighted the role of institutional and technological readiness in enhancing student engagement and learning, and provides insights for refining BL models.